Reaksi Pasar atas Manajemen Laba - Fery Friyo Handoko; Mu'minatus Sholichah (Prodi Akuntansi - FEB Universitas Muhammadiyah Gresik, 2019)
Abstract This research examine the capital market reaction on earnings management. Agency conflict represented by information asymetry caused earnings management. Managers have incentive to play accounting method and estimate to gain certain amount of earnings. Hereafter, investor have interest regarding their invesment decision. They rely on accounting information that represented in financial statement.Based on premise in Signalling Theory, we then hypothesized that investor would response any information addressed to them.Sample and population that used to test hypothesis taken from listed manufacturing company during 2015-2017. We documenting data from financial statement items. We obtain 40 manufacturing company that comply to purposive sampling requirement. We use simple regression to do data analysis. We found the empirical evidence that market reac the earnings management indication. There is empirical fact that cummulative abnormal return decreas when determinate by discretionarry accruals. This research conclude that market reacting the earnings management indication generally.